Natural products as storage media for avulsed tooth - Deepika Jain; Pralhad L Dasar; Sandesh Nagarajappa (Wolters Kluwer Medknow Publications, 2015)
Avulsion of tooth is complete displacement of tooth out of its socket that results in mutilation of periodontal ligaments. The desirable treatment option is replantation of the tooth. However, unsuccessful replantation is a matter of great discontentment. Unsuccessful replantation is due to inappropriate management of the avulsed tooth. Protection of teeth from desiccation due to drying of the periodontal ligament tissue, by keeping it in storage media can improve the outcome of the treatment. This review paper focuses on the use of natural products as storage media for avulsed teeth. In vitro and in vivo research published during 1995-2014, allowing open access on National Center for Biotechnology Information (NCBI) database and articles on EBSCO host (EBSCO-Elton B. Stephens Company) were included. It was found that natural products such as milk, coconut water, propolis, green tea, red mulberry, Aloe vera, egg-white and pomegranate have shown ability to maintain viability of periodontal ligament cells of avulsed teeth. Few natural products such as coconut water and milk can be used in raw form, while other products such as green tea and red mulberry need processing. Ability to maintain periodontal cell viability for a longer time is warranted in cases of major accidents, where teeth can be replanted only after other major surgeries. Natural products have easy availability, greater efficacy and longer storage time as compared to Hank's balanced salt solution which has been recommended by the International Association of Dental Traumatology as standard solution for storage of avulsed teeth. Natural products have shown good qualities in in vitro experiments; further in vivo studies are needed to evaluate their efficacy as storage media.